Potency Of Rice Farming In Lebong Regency Bengkulu Province By Different Cropping System - Putri Suci Asriani; Nyayu Neti Arianti; Ellys Yuliarti; Muhammad Mustofa Romdhon (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2020)
Eventhough wetland rice productivity in Lebong Regency has already been quite high, theneed for rice continues to increase along with population growth. This condition need to behandled by increasing rice production, especially the production of upland rice. This studyaims to study the crop management in rice farming implemented in Lebong Regency andanalyze the production and productivity of rice for every crop management. Research dataare primary data and secondary data collected through Focus Group Discussion involving20 farmer groups . Qualitative data are analysed descriptively by examining theirfarm management focused on variation role of crop and session. The study of cropmanagement pattern in Lebong Regency can be concluded as follows: (1) landmanagement depends on the readiness of farm workers and peasants to work and providecapital so that the cultivated land is limited to the availability of capital owned by farmworkers which is influenced by socio-economic, technical, and market factors, (2) lessoptimal maintenance of centre of production, especially in irrigated rice fields, so thatefforts should be made to increase production and productivity, and (3) lack of synergy indeveloping centre of rice production for staple food providers as a measure of achievementof food security.